2011
DOI: 10.4236/abb.2011.24044
|View full text |Cite
|
Sign up to set email alerts
|

Purification of enzymatically inactive peptidylarginine deiminase type 6 from mouse ovary that reveals hexameric structure different from other dimeric isoforms

Abstract: The murine peptidylarginine deiminase (PAD) has five isoforms encoded by different genes and participates in a variety of cellular functions through the citrullination of target proteins. The crystal structure of human PAD4 with a dimeric form was previously solved because of the enzyme’s relevance to rheumatoid arthritis. PAD6, abundant in mouse oocytes and eggs, is believed to take part in early events of embryogenesis, but its biochemical properties are little understood. Here we have purified and character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…This irreversible PTM leads to a small increase in mass of 0.9840 Da and the loss of a positive charge from the protein which may cause structural and/or functional alterations. Five PAD isoforms have been found in humans, PAD1-4, and the catalytically inactive PAD6 (1), which are believed to have distinct tissue-specificities (2-6). PADcatalyzed citrullination has been implicated in many cellular processes such as terminal epidermal differentiation, apoptosis, central nervous system (CNS) stability, immune response, gene regulation, and embryonic development (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…This irreversible PTM leads to a small increase in mass of 0.9840 Da and the loss of a positive charge from the protein which may cause structural and/or functional alterations. Five PAD isoforms have been found in humans, PAD1-4, and the catalytically inactive PAD6 (1), which are believed to have distinct tissue-specificities (2-6). PADcatalyzed citrullination has been implicated in many cellular processes such as terminal epidermal differentiation, apoptosis, central nervous system (CNS) stability, immune response, gene regulation, and embryonic development (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…There are five human PADs, i.e., PAD1, PAD2, PAD3, PAD4, and PAD6, of which only PADs 1–4 are catalytically active (Raijmakers et al 2007; Taki et al 2011; Witalison et al 2015). These isozymes, which share 50–55% sequence identity within the same species (Arita et al 2004), are found in a myriad of cells and tissue types.…”
Section: Introductionmentioning
confidence: 99%
“…This PTM is generated by a family of calcium-dependent enzymes called protein arginine deiminases (PADs) (Bicker and Thompson 2013; Fuhrmann et al 2015; Fuhrmann and Thompson 2016). There are five human PADs, i.e., PAD1, PAD2, PAD3, PAD4, and PAD6, of which only PADs 1–4 are catalytically active (Raijmakers et al 2007; Taki et al 2011; Witalison et al 2015). These isozymes, which share 50–55% sequence identity within the same species (Arita et al 2004), are found in a myriad of cells and tissue types.…”
Section: Introductionmentioning
confidence: 99%
“…3−5 PAD1 to PAD4 are catalytically active, but PAD6 has no detectable activity. 2,5,6 Although these isozymes share greater than 50% interisozyme sequence identity, 1,5 they display unique tissue expression patterns. 4,7 Significantly, dysregulation of PAD activity has been linked to the pathogenesis of many diseases.…”
mentioning
confidence: 99%
“…Citrullination is a post-translational event involved in many cellular processes such as gene regulation and cell differentiation. , This post-translational modification results in the loss of the net positive charge on the target protein, which leads to structural changes of the protein and consequently alters the protein function and its interaction with other biomolecules. Five human PADs (1, 2, 3, 4, and 6) have been identified and characterized. PAD1 to PAD4 are catalytically active, but PAD6 has no detectable activity. ,, Although these isozymes share greater than 50% interisozyme sequence identity, , they display unique tissue expression patterns. , Significantly, dysregulation of PAD activity has been linked to the pathogenesis of many diseases. ,, …”
mentioning
confidence: 99%